Optimization of the colloidal properties of chitosan nanoparticles encapsulating alpha-arbutin - Shymaa Hatem; Nada ElHoffy; Reham Elezaby; Maha Nasr; Amany Osama; Seham Elkheshen (Ain Shams University, 2022)
Melasma is a highly prevalent skin disorder in which patients exhibit hyperpigmented patches on face. This provokes the essentiality to search for effective treatment strategies, among which are the topical nanosystems. The current study aimed to optimize the prepared chitosan nanoparticles (CSNPs) to enhance the topical delivery as well as the therapeutic potential of alpha-arbutin (α-arbutin), being employed as a skin whitener for melasma treatment. Drug-free nanoparticles were prepared using chitosan polymer and the polyionic tripolyphosphate Sodium salt (TPP) employing the ionic gelation technique. The colloidal properties regarding particle size (P.S), polydispersity index (PDI) and zeta potential (ζ-potential) were evaluated either without adjusting the pH of chitosan or TPP solutions and after its adjustment. The optimized nanoparticles were selected for drug loading. Results revealed that only the TPP concentration had a significant effect on the P.S of drug-free nanoparticles, in which upon increasing its concentration from 0.02 to 0.1%, P.S decreased significantly. Only chitosan concentration affected the EE% of the loaded nanoparticles, in which the increase in chitosan concentration from 0.10 to 0.20% was coupled with significant increase in EE%, however further increase in its concentration from 0.20 to 0.30% resulted in significant decrease in EE%. All formulations exhibited sufficiently positive ζ-potential values ranging from +37.30 to +42.90 mV. The optimization of the nanoparticles revealed that the P.S of CSNPs decreased significantly upon adjusting the pH of both chitosan and TPP solutions. Loading α-arbutin into chitosan solution resulted in significantly higher EE% compared to its loading into TPP solution